Shortening hospital stay for thyroid surgery. (January 2008) - Dionigi, Gianlorenzo; Bacuzzi, Alessandro; Rovera, Francesca; Boni, Luigi; Piantanida, Eliana; Tanda, Maria Laura; Castano, Patrizia; Annoni, Matteo; Bartalena, Luigi; Dionigi, Renzo
The number of outpatient surgical procedures performed in hospitals, increases daily. In some countries, such as Italy, outpatient operations outnumber inpatient operations. The incidence of thyroid disorders and, in particular, the cancer forms, has been increasing sharply for many years in several countries. Even if thyroid surgery is performed with low morbidity, no mortality and short operation time, some potentially lethal complications are strong arguments against shortening of hospital stay. The purpose of this review is to examine the relevant updated published results on the outcome measures that can be used to assess the quality of shortstay surgery for thyroid disease with well-controlled trials. We discuss the special ethical and legal issues that this thyroid surgery raises. Searches were last updated in May 2007.